IMPLEMENTASI DAN IMPLIKASI UNDANG UNDANG NOMOR 23 TAHUN 2011 TENTANG PENGELOLAAN ZAKAT TERHADAP KESEJAHTERAAN MASYARAKAT (Badan Amil Zakat Kota Bandar Lampung) - Nurasari, Nurasari; Mu'in, Fathul; Sulistyani, Ambar (Universitas Islam Negeri Raden Intan Lampung, 2021)
Indonesia is a country with the largest Muslim population in the world. The large number of the Muslim population makes Indonesia has a large potential for zakat. Through zakat, it is hoped that Indonesia will be able to realize the country's goals. As stated in the preamble to the Constitution of the Republic of Indonesia, namely